Critical Evaluation of Information as a New Threshold Concept for Navigating STEM Information. Issue 1 (2nd January 2023) - Mercer, Kate; Weaver, Kari D.
ABSTRACT: When the ACRL Framework was introduced, librarians were challenged to look at the presented threshold concepts and consider how to build on them through practice. STEM librarians have continually grappled with supporting student information seeking in an academic context, while fighting against information overload and misinformation. In social and professional contexts, it is often modeled for students that the fastest information is the best. There is a known implicit recognition of the importance of collaboration between LIS and other disciplines, however there is still a need to navigate various disciplinary silos, and ultimately an opportunity to develop theories and methods that can more fully build out impactful collaborative approaches to teaching information. Critical Evaluation of Information is an introduction to a new, disciplinary situated, threshold concept that is STEM information seeking specific and grounds itself on existing evaluation practices and evaluative frameworks using contextual factors to support students.